PEFA, Public Financial Management, and Good Governance - Kristensen, Jens Kromann (Washington, DC: World Bank, 2019)
This project, based on the Public Expenditure and Financial Accountability (PEFA) data set, researched how PEFA can be used to shape policy development in public financial management (PFM) and other major relevant policy areas such as anticorruption, revenue mobilization, political economy analysis, and fragile states.